2009
DOI: 10.1038/ajh.2008.367
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of First-Fill Adherence for Patients With Hypertension

Abstract: BACKGROUND Between the promise of evidence-based medicine and the reality of inadequate patient outcomes lies patient adherence. Studies of prescription adherence have been hampered by methodologic problems. Most rely on patient self-report of adherence or cross-sectional data of plan-wide prescription fills to estimate patient-level adherence. METHODS We conducted a retrospective cohort study and linked individual patient data for incident prescriptions for antihypertensive medications from electronic healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 13 publications
6
64
2
5
Order By: Relevance
“…Two studies of large populations of patients in different clinical settings found PMN rates over 20%, 16,17 and studies of PMN for patients in the Geisinger system found PMN rates of 15%-17% among patients prescribed antihypertensive and oral diabetes medications. 20,21 Our considerably lower PMN rates are similar to those seen in recent reports from other integrated health care settings, [22][23][24] suggesting perhaps the structure of the health system or the use of e-prescribing was a factor in first-fill rates. However, a key difference between these studies and ours is the use of primarily in-network pharmacies versus our use of an independent pharmacy chain.…”
Section: ■■ Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Two studies of large populations of patients in different clinical settings found PMN rates over 20%, 16,17 and studies of PMN for patients in the Geisinger system found PMN rates of 15%-17% among patients prescribed antihypertensive and oral diabetes medications. 20,21 Our considerably lower PMN rates are similar to those seen in recent reports from other integrated health care settings, [22][23][24] suggesting perhaps the structure of the health system or the use of e-prescribing was a factor in first-fill rates. However, a key difference between these studies and ours is the use of primarily in-network pharmacies versus our use of an independent pharmacy chain.…”
Section: ■■ Discussionsupporting
confidence: 71%
“…Unexpectedly, 94% of patients picked up their index prescription before becoming eligible for the study (4,532/4,822), a much lower rate of PMN than found in prior observational studies either in the Geisinger system or elsewhere. 20,21 The low rate of PMN resulted in much slower than anticipated addition of patients to the study population, with final total enrollment of 290 patients rather than the prespecified target of 298. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two other recent studies of adherence to new prescriptions for diabetes and hypertension among patients treated in a single health system found non-adherence rates similar to those seen in our study. 2,3 As with the comparison between our findings and those of Karter et al, it is difficult to be certain whether these findings reflect some characteristics unique to the study setting as opposed to more universal behaviors around prescription filling. We agree that more such studies will be needed, both to improve the methods used for identifying primary non-adherence and to develop more robust estimates of the prevalence of this phenomenon in a wide variety of real-world practice settings.…”
contrasting
confidence: 49%
“…13,14 Studies in closed health care systems have found slightly lower rates of PMN (15%-26%), although the problem is still substantial. [15][16][17] Once PMN can be identified and measured, the challenge is to identify interventions specifically targeting PMN. Systematic reviews of the adherence literature indicate that community pharmacists can play an important role.…”
Section: Resultsmentioning
confidence: 99%